2016
DOI: 10.1038/ncomms12433
|View full text |Cite
|
Sign up to set email alerts
|

DELLA proteins are common components of symbiotic rhizobial and mycorrhizal signalling pathways

Abstract: Legumes form symbiotic associations with either nitrogen-fixing bacteria or arbuscular mycorrhizal fungi. Formation of these two symbioses is regulated by a common set of signalling components that act downstream of recognition of rhizobia or mycorrhizae by host plants. Central to these pathways is the calcium and calmodulin-dependent protein kinase (CCaMK)–IPD3 complex which initiates nodule organogenesis following calcium oscillations in the host nucleus. However, downstream signalling events are not fully u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
196
1
11

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(221 citation statements)
references
References 67 publications
13
196
1
11
Order By: Relevance
“…Other reports showed that exogenous application of GA 3 inhibited NFs‐induced root hair deformation, infection thread formation and nodule development in L. japonicus and M. truncatula . Application of paclobutrazol (PAC), an inhibitor of GA biosynthesis, rescued this phenotype (Maekawa et al ; Fonouni‐Farde et al ; Jin et al ), which indicates negative regulation of GAs at infection thread formation and nodule development.…”
Section: Gibberellinmentioning
confidence: 99%
See 3 more Smart Citations
“…Other reports showed that exogenous application of GA 3 inhibited NFs‐induced root hair deformation, infection thread formation and nodule development in L. japonicus and M. truncatula . Application of paclobutrazol (PAC), an inhibitor of GA biosynthesis, rescued this phenotype (Maekawa et al ; Fonouni‐Farde et al ; Jin et al ), which indicates negative regulation of GAs at infection thread formation and nodule development.…”
Section: Gibberellinmentioning
confidence: 99%
“…Recently, we showed that DELLA proteins, the central negative regulators of the GA signaling pathway, act as a common component of rhizobial symbiosis and mycorrhizal symbiosis (Jin et al ). Triple Mtdella mutants exhibited a strong impairment in infection thread formation and nodule development and induced most NFs‐inducible genes (Jin et al ).…”
Section: Gibberellinmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Chinese scientists have made significant progress in terms of mycorrhizal signal transduction, for example, some specific proteins such as DELLA and CERK1, were found to be common components of symbiotic mycorrhizal signalling pathways and to play critical function during the establishment of symbiosis between AM fungi and host plants (e.g. Yu et al 2014; Zhang et al 2015; Jin et al 2016). …”
Section: Molecular Biology Of Mycorrhizal Fungimentioning
confidence: 99%